ANALISIS KESESUAIAN LAHAN DAN DAYA DUKUNG EKOWISATA MANGROVE DI KAWASAN MANGROVE MUARA KUBU, KALIMANTAN BARAT - Teguh Setyo Nugroho (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
Muara Kubu mangrove ecosystem area has a unique value, aesthetic, beauty that has the potential to be developed ecotourism. In the development of mangrove ecotourism, the main step that needs to be studied is the identification of ecotourism conditions and potentials in the area through an analysis of land suitability and ecotourism carrying capacity. The purpose of this study is to determine the land suitability and carrying capacity of mangrove ecotourism at Muara Kubu mangrove areas. The method used in this research is quantitative descriptive with data collection through observation and field survey. Land suitability analysis of the mangrove ecotourism is done spatially based on the multiplication of scores and weights obtained from each paremeter with Geographic Information System (GIS) approach. Analysis of ecotourism carrying capacity is calculated by equation of Regions Carrying Capacity  (RCC). The research results showed that the area of mangrove vegetation cover in Muara Kubu area is 3695,85 hectares with coastal length ± 25,45 km. The total land suitability of mangrove ecotourism in Muara Kubu area is 3,617.97 hectares. The carrying capacity of mangrove ecotourism in Muara Kubu mangrove area is 2035 people per day